Communication Education of Learning Media Analysis Using Science Edutainment Approach - Nofha Rina (Lingkar Studi Komunikasi (LISKI), 2021)
The rapid advancement of ICT offers various conveniences in learning, allowing a shift in learning orientation from outside-guided to self-guided and from knowledge-as-possession to knowledge-asconstruction. To support learning in the classroom, supporting facilities and infrastructure are needed in the form of tools or media. In the world of education, the terms tools or communication media are often used interchangeably or as a substitute for the term educational media learning. The method used to achieve the goal is through development research directed at developing environmental-themed social studies learning media for Bandung City Junior High School (SMP) students, in the form of ICT-based puzzles, crosswords and squarewords. The subjects were 30 junior high school students aged 13-15 years which were divided into experimental and control groups. The results of this study are important as a new study in finding the development of learning media with a science-edutainment approach. Keywords: Media Learning, Thematic, Environment, Science-Edutainment